2019
DOI: 10.1093/ckj/sfz145
|View full text |Cite
|
Sign up to set email alerts
|

Cellular origin and microRNA profiles of circulating extracellular vesicles in different stages of diabetic nephropathy

Abstract: Background Diabetic nephropathy (DN) is a major complication of diabetes and the main cause of end-stage renal disease. Extracellular vesicles (EVs) are small cell-derived vesicles that can alter disease progression by microRNA (miRNA) transfer. Methods In this study, we aimed to characterize the cellular origin and miRNA content of EVs in plasma samples of type 2 diabetes patients at various stages of DN. Type 2 diabetes pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…In vitro, EVs rich in miR-21 improved endothelial barrier formation of cells cultured in serum from patients with DM and DKD [ 97 ]. Similar studies by Uil M et al described the upregulation of miR-99a-5p in EVs of macroalbuminuric patients compared with normo- and microalbuminuric subjects [ 95 ]. Moreover, the transfection of the miR-99a-5p mimic to cultured podocytes induced a downregulation of mTOR and the injury marker vimentin, suggesting a protective effect of miR-99a-5p on glomerular cells [ 95 ].…”
Section: Circulating Evs In Diabetic Kidney Diseasesupporting
confidence: 56%
See 2 more Smart Citations
“…In vitro, EVs rich in miR-21 improved endothelial barrier formation of cells cultured in serum from patients with DM and DKD [ 97 ]. Similar studies by Uil M et al described the upregulation of miR-99a-5p in EVs of macroalbuminuric patients compared with normo- and microalbuminuric subjects [ 95 ]. Moreover, the transfection of the miR-99a-5p mimic to cultured podocytes induced a downregulation of mTOR and the injury marker vimentin, suggesting a protective effect of miR-99a-5p on glomerular cells [ 95 ].…”
Section: Circulating Evs In Diabetic Kidney Diseasesupporting
confidence: 56%
“…Similar studies by Uil M et al described the upregulation of miR-99a-5p in EVs of macroalbuminuric patients compared with normo- and microalbuminuric subjects [ 95 ]. Moreover, the transfection of the miR-99a-5p mimic to cultured podocytes induced a downregulation of mTOR and the injury marker vimentin, suggesting a protective effect of miR-99a-5p on glomerular cells [ 95 ]. Sequencing of circulating EVs found a different miRNA profile in healthy volunteers compared to diabetic patients with DKD [ 98 ].…”
Section: Circulating Evs In Diabetic Kidney Diseasesupporting
confidence: 56%
See 1 more Smart Citation
“…Studies have increasingly proven that the expression of circulating miRNAs is dysregulated in various diseases, and miRNAs have been considered promising novel biomarkers for the diagnosis and monitoring of almost all diseases, including DN. [22][23][24][25] The miR-29 family comprises miR-29a, miR-29b and miR-29c, of which miR-29a and miR-29b are transcribed from chromosome 7q32. In this study, we found that the basic indicators of blood pressure and serum lipids in the T2DM patients were significantly increased compared with those in the healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) constitute a group of noncoding singlestranded small RNA molecules with a length of approximately [21][22][23][24][25] nucleotides that can regulate the expression of target genes through the complete or partial complementary binding of the 3' untranslated region of the target messenger RNA. 7,8 Strikingly, human serum/plasma contains numerous stably expressed miRNAs and has the biological properties of resistance to RNase activity; thus, miR-NAs derived from peripheral blood have the potential to become noninvasive biomarkers of various diseases.…”
mentioning
confidence: 99%